Factors influences consumer perceptions towards online purchase intentation: A study in Kota Kinabalu, Sabah - Stephanie Kunsiong (2011)
The purpose of this study is to test the relationship between factors (security, brand awareness, word of mouth, good online experience and quality of information) that might influence customer perceptions to online purchase intention. The framework of this study was adapted from (Ha, 2004). This study will be conducted in Kata Kinabalu, Sabah with working female and male or also known as Working Age Group ages from 18 until 64 will be a sample to complete this study. 384 questionnaires were distributed to the government and private sector and only 309 were valid for data processing. 54 respondents' answer 'no' in screening question and could not be processing. From the result get, it was discovered that not all the online purchase intention determinants were found to be significant in the relationship between online purchase intentions. Marketers may find this information beneficial as they can consider using it to plan better marketing strategies to attract and retain customer perceptions towards online purchase intention until they perform into final behavior which is making a purchasing.